Symmetrization of the backbone of nucleic acids: a molecular dynamics study. Issue 3 (11th February 2020) - Pant, Pradeep; Pathak, Amita; Jayaram, B.
Abstract: DNA displays directional asymmetry (5'→3'), a fundamental property associated with each strand of the nucleic acids and is crucial to several biological processes such as transcription and replication. We observe that this asymmetry can be altered by a number of ways leading to directionally symmetric nucleic acids. We report six such approaches for the creation of symmetric backbones, their insertion in a regular B-DNA structure followed by their characterization using molecular dynamics (MD) simulations on a microsecond timescale in explicit solvent. We compared the resultant MD structures of symmetric nucleic acids with that of regular B-DNA in terms of helicoidal parameters, dihedrals, groove geometry, and solvent/ions accessibility. We also compared the Watson-Crick hydrogen bond strength of these symmetric molecules to that of the control B-DNA system. It was found that the symmetric DNAs with a few substituents designed retained the double helical B-DNA type structure as seen by means of structural and energetic parameters. As an application of such symmetric molecules, we evaluated the binding free energies of single stranded symmetric nucleic acids with a short stretch of complementary RNA and found that a few molecules designed have comparable energies to that of control DNA-RNA hybrid system. As the chemical modifications in the oligonucleotides have been a remarkable tool for control over the nucleotide properties, mainly the nucleotide bending, binding to RNA targets, and stability to nucleases to design nucleoside drug analogs; the importance of the proposed symmetric molecules in these areas is foreseen. Communicated by Ramaswamy H. Sarma